2013
DOI: 10.1109/lawp.2013.2270949
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a Circular Loop Antenna in the Presence of a Coaxial Conducting BOR Attached to a Planar Reflector

Abstract: The performance of the circular loop antenna (CLA) largely improves in terms of impedance matching and directive gain when a body of revolution (BOR)-type of reflector is placed symmetrically relative to the loop. The input impedance, reflection coefficient, VSWR, directivity, and radiation patterns of a loop antenna for cases of a reflector-hemisphere and a reflector-cone are investigated in this letter. It is found that for a resonant loop, directivity over 9 dB and VSWR less than 2 over a bandwidth of 48.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Research on the loop antenna analysis method has been conducted by Sen et al, about the general method of current excitation reconstruction in cylindrical antenna arrays [13], Joshi and Behera about the method of moment analysis in circular loop linear arrays and loop arrays [14]. Research on the characteristics of circular loop antennas has been carried out by Hamed and Bashir on the characteristics of circular loop antennas [15], Salem, and Caloz about the emission of electromagnetic fields by arbitrary currents in circular loops [16]. Research on loop antenna applications has been conducted by Vembarasi et al regarding the design of bi-circular antennas as wideband antennas [17], Zheng et al about the use of loop wire antenna as an orbital angular momentum generator [18].…”
Section: The Increasing Need Of Modern Society For Communication and mentioning
confidence: 99%
“…Research on the loop antenna analysis method has been conducted by Sen et al, about the general method of current excitation reconstruction in cylindrical antenna arrays [13], Joshi and Behera about the method of moment analysis in circular loop linear arrays and loop arrays [14]. Research on the characteristics of circular loop antennas has been carried out by Hamed and Bashir on the characteristics of circular loop antennas [15], Salem, and Caloz about the emission of electromagnetic fields by arbitrary currents in circular loops [16]. Research on loop antenna applications has been conducted by Vembarasi et al regarding the design of bi-circular antennas as wideband antennas [17], Zheng et al about the use of loop wire antenna as an orbital angular momentum generator [18].…”
Section: The Increasing Need Of Modern Society For Communication and mentioning
confidence: 99%
“…The study of the performance of CLAs carrying different forms of current and in the presence of discontinuities has been considered in many studies such as the loop near a planar interface [1,2], the loop in front of a resistive sheet [3], the loop above a lossless ground plane [4] and a circular loop on a lossy half space [5]. Investigation of the performance of CLAs around conducting body has been conducted for a thin loop on multilayered spheroid media [6], a single CLA neighbouring a cylinder, a sphere or a cone in [7], a CLA in the presence of a coaxial conducting body of revolution attached to a planar reflector in [8] and multiple circular loops around a conducting cone in [9].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial dyadic Green's has been proposed to investigate the patch antennas in a layered spherical media [18,19]. Despite the accuracy and efficiency of these integral methods, a few of them have been interested in the analysis of CLA around multilayer dielectric sphere [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…al. [11,12] have shown that the presence of a conducting body of revolution type reflectors near a loop antenna can improve both antenna directivity and VSWR. Even though extensive research is conducted on loop antenna arrays and systems as Yagi-Uda and log periodic arrays, seldom published work on concentric loop array configuration can be found.…”
Section: Introductionmentioning
confidence: 99%